2023
DOI: 10.3390/jcm12041591
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Supplementation with Standardized Terminalia chebula Fruit Extracts Reduces Facial Sebum Excretion, Erythema, and Wrinkle Severity

Abstract: Terminalia chebula (TC) is a medicinal plant that exhibits antioxidant, anti-inflammatory, and antibacterial properties and that is widely used in Ayurveda and herbal formulations. However, the skin effects of TC as an oral supplement have not been studied. The objective of this study is to determine if oral TC fruit extract supplementation can modulate the skin’s sebum production and reduce the appearance of wrinkles. A prospective double-blind placebo-controlled study was conducted on healthy females aged 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…They found that treatment with the aqueous extracts of Indian almonds exhibited antihepatotoxic activity against carbon tetrachloride (CCl4)-induced toxicity in the rat. Chakkalakal et al, [25] stated that the multiple antioxidant effects of the tannin components from Indian almonds have the capability to prevent lipid peroxidation (LPO), and formation of superoxide. Punicalin and punicalagin are the most copious phyto constituents and have the effective antioxidant activity of T. catappa.…”
Section: Discussionmentioning
confidence: 99%
“…They found that treatment with the aqueous extracts of Indian almonds exhibited antihepatotoxic activity against carbon tetrachloride (CCl4)-induced toxicity in the rat. Chakkalakal et al, [25] stated that the multiple antioxidant effects of the tannin components from Indian almonds have the capability to prevent lipid peroxidation (LPO), and formation of superoxide. Punicalin and punicalagin are the most copious phyto constituents and have the effective antioxidant activity of T. catappa.…”
Section: Discussionmentioning
confidence: 99%
“…Individual typological angle (ITA) and melanin index (MI) measurements were obtained using a colourimeter, the SkinColorCatch (Delfin Technologies, Surrey, United Kingdom). The SkinColorCatch is a clinical instrument and colourimeter that is extensively used to determine facets of skin tone reliably in both in vitro (56) and in vivo settings (59)(60)(61)(62). The readings were repeated three times in different surface areas to get an average value of the parameter.…”
Section: Individual Typological Angle and Melanin Index Readingsmentioning
confidence: 99%